PEMANFAATAN EKSTRAK DAUN KETAPANG (Terminalia catappa L.) SEBAGAI HERBISIDA ALAMI DALAM PERSPEKTIF ILMU LINGKUNGAN (EKOLOGI, SOSIAL, DAN EKONOMI) UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN - Iga Azalia Lamonda; Tengku Nurhidayah; Rahman Karnila (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2025)
The intensive use of chemical herbicides in agriculture has caused serious impacts on the environment, human health and ecosystem sustainability. These impacts include soil, water, and air pollution, as well as health risks due to exposure to hazardous active ingredients. As a solution, this study examines the potential of ketapang (Terminalia catappa L.) leaf extract as an environmentally friendly organic herbicide. The content of allelochemical compounds in ketapang leaves is proven to effectively inhibit weed growth, and is safer and more economical than synthetic herbicides. Thus, ketapang extract herbicide is considered to have high prospects as an alternative weed control that supports sustainable agriculture. This study aims to identify the optimal formulation and concentration of natural herbicides of ketapang leaf extract in suppressing weed growth, analysing the percentage of live, height, number of shoots, wet weight, and dry weight of weeds. The research was conducted at UNRI Gobah Campus and the author's house in Pekanbaru. The environmental aspects used 4 x 2 factorial RAL with 3 replications, factors of herbicide concentration (Gramoxone, ketapang extract 25%, 50%, 75%) and weed species (Cynodon dactylon L. and Cyperus rotundus). Data were analysed with variance analysis and 5% Duncan test. The results showed that the 75% concentration of ketapang leaf extract herbicide was effective in suppressing weed growth and could replace chemical herbicides still used by farmers, although the effect was not as fast as chemical herbicides in killing weeds. Especially on the percentage of live weeds, weed height, and weed species. The interaction between ketapang leaf extract herbicide and weed type was effective in suppressing weed growth but not on wet weight and dry weight of weeds. The use of ketapang leaf extract is more recommended because it can be used as an alternative to replace the use of chemical herbicides that are environmentally friendly and safe for health